2015
DOI: 10.1097/qai.0000000000000603
|View full text |Cite
|
Sign up to set email alerts
|

Injection Drug Use and Hepatitis C as Risk Factors for Mortality in HIV-Infected Individuals

Abstract: Background HIV-infected individuals with a history of transmission via injection drug use (IDU) have poorer survival than other risk groups. The extent to which higher rates of hepatitis C (HCV) infection in IDU explain survival differences is unclear. Methods Adults who started antiretroviral therapy (ART) between 2000-2009 in 16 European and North American cohorts with >70% complete data on HCV status were followed for 3 years. We estimated unadjusted and adjusted [for age, sex, baseline CD4 count and HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 35 publications
2
36
1
2
Order By: Relevance
“…As such, we were able to assume with confidence that those lost to follow-up were not dead allowing us to estimate a rate of lost to follow-up that was not different among the studied groups. We excluded patients reporting injection drug use/heavy cocaine use given its known association with mortality (5). This allowed us to study mortality among women, heterosexual men and MSM without the confounding effect of drug use but precluded an analysis of this particular risk factor which may differ by sex and/or sexual mode of transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, we were able to assume with confidence that those lost to follow-up were not dead allowing us to estimate a rate of lost to follow-up that was not different among the studied groups. We excluded patients reporting injection drug use/heavy cocaine use given its known association with mortality (5). This allowed us to study mortality among women, heterosexual men and MSM without the confounding effect of drug use but precluded an analysis of this particular risk factor which may differ by sex and/or sexual mode of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, HIV-infected adults who report transmission through injection drug use have been shown to have significantly higher risk of mortality compared to other modes of transmission (5). In contrast, differences in mortality between heterosexual men and MSM with HIV infection have not been well described.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, incarceration [1**,43] and personal violence [3**,7,10*] remain persistent issues among HIV-positive PWID, with research demonstrating increased rates of suicides [7,44] being independently associated with a history of IDU (adjusted hazard ratio: 3.95; confidence interval: 1.99 – 7.86) [44]. Studies conducted in settings without universal healthcare may not be able to distinguish the effect of the aforementioned factors independent of the influence of financial need.…”
Section: Hiv/aids-related Mortality In the Modern Treatment Eramentioning
confidence: 99%
“…Despite advances in availability and tolerability of treatment, mortality remains high among HIV- positive PWID when compared with other key populations of PLHIV, in low-, middle-, and high-income settings [69,10*,11,12,13*,14,15,16*,1723]. For example, across the 16 European and North American cohorts in the Antiretroviral Therapy Cohort Collaboration, which comprise 32 703 HIV-positive adults who started ART between 2000 and 2009, all- cause mortality among people with a history of injection drug use (IDU) was more than twice that of individuals with no history of IDU [10*]. Such stark inequities are especially troubling in the context of healthcare settings with well established ART delivery systems, programming, and supports for individuals who experience barriers to treatment adherence.…”
Section: Introductionmentioning
confidence: 99%
“…While chronic hepatitis C virus (HCV) may account for much of this mortality 2,3 , an excess burden of liver disease has been reported in HIV monoinfected patients. 48 Multiple studies have demonstrated accelerated progression to cirrhosis in HIV-HCV coinfected patients compared with HCV-monoinfected patients 9 , and that ART mitigates the progression of liver disease in coinfected patients.…”
Section: Introductionmentioning
confidence: 99%